METHODOLOGICAL PRINCIPLES OF BUILDING AN ORGANIZATIONAL AND ECONOMIC MECHANISM FOR DEVELOPING THE ECONOMIC POTENTIAL OF AGRICULTURAL ENTERPRISES - KALINICHENKO, Sergiy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article substantiates the methodological principles for developing an organizational and economic mechanism to enhance the economic potential of agricultural enterprises in conditions of structural changes and instability in the resource environment. The significance of regional differentiation in the process of developing management decisions is revealed, driven by differences in enterprise resource provision and the heterogeneity of the institutional environment in Ukraine. It is proven that the mechanism’s effectiveness largely depends on the enterprise’s ability to account for the influence of informal institutions and the level of institutional risks, which determine the effectiveness of economic strategies. Special attention is paid to balancing stimulating and regulatory instruments that ensure the optimal combination of economic, social, and environmental goals. Coordination of these components allows the formation of a three-dimensional equilibrium necessary for the sustainable development of agricultural enterprises. A conceptual multi-block architecture for the organizational and economic mechanism is proposed, comprising methodological, functional, and instrumental blocks that ensure the consistency of management decisions with the enterprise’s structure and culture. The importance of phased management of economic potential is substantiated, from setting strategic goals and resource provision to monitoring results. This approach enhances the adaptability of agricultural enterprises to external challenges and strengthens their competitiveness. The formulated methodological principles serve as the basis for improving the mechanisms of strategic development of Ukraine’s agrarian sector.